High Crystalline Quality Perovskite Thin Films Prepared by a Novel Hybrid Evaporation/CVD Technique. Issue 1771 (2015) - Peng, Yanke; Jing, Gaoshan; Cui, Tianhong
ABSTRACT: Performance of a perovskite based solar cell is highly determined by the crystalline qualities of the perovskite thin film sandwiched between an electron and a hole transport layer, such as grain size and uniformity of the film. Here, we demonstrated a new hybrid physical-chemical vapor deposition (HPCVD) technique to synthesis high quality perovskite films. First, a PbI2 precursor film was spin-coated on a mesoporous TiO2 (m-TiO2 )/compact TiO2 (c-TiO2 )/FTO substrate in ambient environment. Then, purified CH3 NH3 I crystal material was evaporated and the vapor reacted with the PbI2 precursor film in a vacuum pressure/temperature accurately controlled quartz tube furnace. In this technique, high vacuum (2mTorr) and low temperature (100°C) were applied to decrease perovskite film growth rate and reduce perovskite film defects. After vapor reaction, the perovskite film was annealed at 100°C for 10min in 20mTorr vacuum to recrystallize and remove CH3 NH3 I residue in order to further improve crystal quality of the thin film. Crystal quality of this perovskite thin film was characterized by scanning electron microscopy (SEM), atomic force microscopy (AFM), and X-ray diffraction (XRD). SEM and AFM results illustrate perovskite thin films synthesized by this technique have larger grain sizes and more uniformity (RMS 11.6nm/Ra 9.3nm) superior to most existing methods. Strong peaks shown in the XRD chart at 14.18°, 28.52°, 31.96°, which were assigned to (110), (220), (330) miller indices of CH3 NH3 PbI3 perovskite crystal, indicate the complete reaction between CH3 NH3 I vapor and PbI2 precursor layer. High power conversion efficiency (PCE) up to 12.3% and stable efficiencies under four hours illumination of AM1.5 standard were achieved by these solar cells. This vacuum/vapor based technique is compatible with conventional semiconductor fabrication techniques and high quality perovskite film could be achieved through delicate process control. Eventually, perovskite based solar cells could be mass produced in low cost for large scale applications by this novel technique.